5G-Enabled Tactile Internet for smart cities: vision, recent developments, and challenges - Alam, Tanweer (Jurnal Informatika, 2019)
The Tactile Internet (TI) is an emerging technology next to the Internet of Things (IoT). It is a revolution to develop smart cities, communities, and cultures in the future. This technology will allow the real-time interaction between humans and machines as well as machine-to-machine with the 1ms challenge to achieve in round trip latency. The term TI is defined by the International Telecommunication Union (ITU) in August 2014. The TI provides a fast, reliable, secure and available internet network that is the requirements of the smart cities in 5G. Tactile internet can develop the part of the world where the machines are strong, and humans are weak. It increases the power of machines so that the value of human power will increase automatically. In this framework, we have presented the idea of tactile internet for the next generation of smart cities. This research will provide a high-performance reliable framework for the internet of smart devices to communicate with each other in a real-time (1ms round trip) using IEEE 1918.1 standard. The objective of this research is expected to bring a new dimension in the research of smart cities.